Complete Asymptotics of the Deviation of a Class of Differentiable Functions from the Set of Their Harmonic Poisson Integrals - Zhyhallo, K. M.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
On a class of differentiable functions W r and the class \(W ^r \) of functions conjugate to them, we obtain a complete asymptotic expansion of the upper bounds \(E(N,Aρ )_C \) of deviations of the harmonic Poisson integrals of the functions considered.